If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 14 = -33 Reorder the terms: 14 + Y = -33 Solving 14 + Y = -33 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + Y = -33 + -14 Combine like terms: 14 + -14 = 0 0 + Y = -33 + -14 Y = -33 + -14 Combine like terms: -33 + -14 = -47 Y = -47 Simplifying Y = -47
| -15y+9x=105 | | -12=0.4x-0.7x | | 3x^2-4x+16=0 | | K-9=-4 | | 9x-15y=105 | | -4(4-7x)+7=-9+7x | | -2x+8=8-x | | x+3x-3y=0 | | -161=-14x-9x | | X+158=180 | | 4.5-x=6 | | 2(x+3)=1-2x | | 161=14x-9x | | -3(x+5)=8+18 | | y=(2x-15)+2 | | 8y^2-18y+7=0 | | X+160=180 | | 2p-7=13+6p | | 1-7(6-5x)=4(6-x)-10X | | -5(7x+2)=-5x-40 | | -r-16r=136 | | 0.3(2h+3)=5 | | 7n^2+22n-24=0 | | 9y-2y=28 | | 10x+2=9x^2 | | n^2-6n-7=0 | | -4(m-23)=5 | | 0.8x=5.6 | | -3=10+x | | 0.6(x+1)=-8 | | 4a+-10=42 | | (5a-6)(5a-6)=0 |